Post-COVID-19 pandemic organ donation activities in Germany: a multicenter retrospective analysis - Englbrecht, Jan Sönke; Schrader, Daniel; Alders, Jörg Benedikt; Schäfer, Melanie; Soehle, Martin (Frontiers in Public Health, 2024)
Introduction: The COVID-19 pandemic had a negative impact on the number of solid organ transplantations. After a global decline of 16% in 2020, their numbers subsequently returned to pre-pandemic levels. In contrast, numbers in Germany remained almost constant in 2020 and 2021 but fell by 6.9% in 2022. The reasons for this divergent development are unknown. Methods: The number of deceased with a severe brain damage, potential and utilized donors after braindeath and the intensive care unit treatment capacity were retrospectively compared for the years 2022 and 2021 at five university hospitals in North Rhine-Westphalia, Germany. Reasons for a donation not utilized were reviewed. To enable a comparison of the results with the whole of Germany and the pre-pandemic period, numbers of potential and utilized donors were extracted from official organ donation activity reports of all harvesting hospitals in Germany for the years 2019 to 2022. Results: The numbers of deceased with a severe brain damage (-10%), potential (-9%) and utilized donors after braindeath (-44%), and intensive care unit treatment capacities (-7.2%) were significantly lower in 2022 than 2021. A COVID-19 infection was a rarer (-79%), but donor instability (+44%) a more frequent reason against donation in 2022, whereas preserved brain stem reflexes remained the most frequent reason in both years (54%). Overall numbers of potential and utilized donations in Germany were lower in 2022 than in the pre-pandemic period, but this was mainly due to lower numbers in hospitals of lower care. The number of potential donors in all university hospitals were higher in 2022 but utilized donations still lower than in 2019. Conclusion: The decrease in potential and utilized donations was a result of reduced intensive care unit treatment capacities and a lower conversion rate at the five university hospitals. A COVID-19 infection did not play a role in 2022. These results indicate that ICU treatment capacities must be restored to increase donations. The lower number of potential donors and the even lower conversion rate in 2022 throughout Germany show that restructuring the organ procurement process in Germany needs to be discussed to increase the number of donations.